2018
DOI: 10.2147/ijn.s165565
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic quantum dot-labeled B16F10 murine melanoma cells as a tool to monitor early steps of lung metastasis by in vivo imaging

Abstract: BackgroundNumerous studies have proposed the use of fluorescent semiconductor nanoparticles or quantum dots (QDs) as novel tools to label cells and tumors. However, QD applications are limited by their toxicity in biological systems and little is known about whether QDs affect the capacity of cancer cells to metastasize. Previously, we described the “biomimetic” synthesis of CdTe-QDs (QDs-glutathione [GSH]) with increased biocompatibility and the potential utility in labeling cells.PurposeIn order to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…CAV1 has been suggested to promote melanoma metastasis by enhancing extravasation [40]. Consistent with the latter findings, we have shown that CAV1 promotes transendothelial migration in vitro [29] and very early events in lung colonization by melanoma cells [41]. Indeed, we observed here that CAV1-enhanced transendothelial migration of melanoma cells is blocked by CGP42112 treatment.…”
Section: Discussionsupporting
confidence: 91%
“…CAV1 has been suggested to promote melanoma metastasis by enhancing extravasation [40]. Consistent with the latter findings, we have shown that CAV1 promotes transendothelial migration in vitro [29] and very early events in lung colonization by melanoma cells [41]. Indeed, we observed here that CAV1-enhanced transendothelial migration of melanoma cells is blocked by CGP42112 treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The B16F10 cells we applied is the most widely used cell type of melanoma with an elevated metastatic potential that acts as a well-established preclinical model for evaluating the anti-melanoma efficacy of therapeutics. 24 This model has important benefits over xeno-transplantation or genetically modified models since mice possess a normal immune system that opens a useful platform for new therapies and adequate host response. 25 Moreover, B16F10 tumor growth drives pro-inflammatory response and muscle loss that are associated with impaired skeletal muscle strength and decreased locomotion and exploratory activity in B16F10 tumor-bearing mice, promoting cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the fluorescence sensibility of QDs is two to three times higher than most organic fluorophores commonly used in live imaging (Díaz‐García et al . 2018), a situation that has favoured their use as a fluorescent tool for in vivo assays. The surfaces of QDs can be modified, improving their active targeting, or the addition of diagnostic or therapeutic groups (Akerman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Our red and green biomimetic fluorescent NPs were used to track metastatic cells in mice with no effect on animal viability (Díaz‐García et al . 2018). QDs‐labelled B16F10 cells remained viable for at least 5 days and migrated similarly to control cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation